Dynamical Behavior of Two Predators-One Prey Ecological System with Refuge and Beddington –De Angelis Functional Response - Majeed, Saba Noori; Naji, Raid Kamel (Iraqi Journal of Science, 2023)
The dynamical behavior of an ecological system of  two predators-one prey updated with incorporating prey refuge and Beddington –De Angelis functional response had been studied in this work, The essential mathematical features of the present model have been studied  thoroughly. The system has local and global stability when certain conditions are met.  had been  proved respectively.  Further, the system has no saddle node bifurcation but transcritical bifurcation and Pitchfork bifurcation are satisfied while the Hopf bifurcation does not occur. Numerical illustrations are performed  to validate the model's applicability under consideration. Finally, the results are included in the form of points in agreement with the obtained numerical results.